Construction Suitability of Trammel Net Operated by Kotabaru Fisherman Based on SNI 01-7237-2006 - Rihmi, Mihrobi Khalwatu; Akbar, Hidayatul Aisytu Nurul; Harlyan, Ledhyane Ika; Lelono, Tri Djoko (Journal of Fish Health, 2025)
Trammel net is a type of gill net. Usually, fishermen operate trammel nets to catch shrimp. Many fishermen build trammel nets traditionally without going through a standard design and construction process. They bought webbing on the market to assemble them into three layers of net and equipped with rope components and buoys, sinker, and selvedge. Meanwhile, to realize the effectiveness of fishing and managing fisheries activities, the government regulates the standard form of trammel net through SNI 01-7237-2006. Thus, it is necessary to evaluate the suitability of the standard form of trammel net based on SNI rules. This research was conducted using a quantitative descriptive method. The research locations are in three villages which are fishing bases for trammel net fishermen in Kotabaru Waters, namely: Pantai Village; Salino Village; and Sungai Pasir Village. The results from the three trammel net sample sizes: small; medium and large have scores of 89%; 95%; and 95% which are in the very suitable category.